Tail causalities between monetary supply and real estate prices in China. Issue 1 (2nd January 2020) - Ding, Haoyuan; Liang, Guoyong; Qi, Tong; Ying, Jiezhou
Abstract: The asymmetric and segmented causality between the monetary policy and real estate market in China is crucial but remains mystery. With the application of quantile causality test, this article investigates nonlinear dependence between property prices and money supply. Our results show that the tail causality exists in many cities in China. Moreover, we find that small-sized cities and inland cities are more sensitive to the broad money (M2) changes when the housing market return is in the tail quantile intervals. These findings can help the Chinese government formulate appropriate monetary policies regarding their implications in the real estate market.